2021
DOI: 10.1002/solr.202000693
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Resolved Effective Majority Carrier Mobility in Highly Anisotropic Antimony Chalcogenide Thin‐Film Solar Cells

Abstract: Majority carrier mobility is one of the most fundamental and yet important carrier transport parameters determining the optimal device architecture and performance of the emerging antimony chalcogenide solar cells. However, carrier mobility measurements based on the Hall effect have limitations for these highly anisotropy materials due to the discrepancy of transport directions under Hall measurement and device operation. Herein, a defect‐resolved mobility measurement (DRMM) method enabling the evaluation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The effective carrier mobility in our Sb 2 (S,Se) 3 absorber may be even lower than the value reported in ref. 8. Therefore, a high-quality HTL is essential for efficient carrier collection of high-efficiency devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective carrier mobility in our Sb 2 (S,Se) 3 absorber may be even lower than the value reported in ref. 8. Therefore, a high-quality HTL is essential for efficient carrier collection of high-efficiency devices.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Due to the highly anisotropic quasi 1D structure and the associated low effective carrier mobility of Sb 2 (S,Se) 3 , an n-i-p device structure with a fully depleted absorber and enhanced carrier collection via an extended built-in electric eld is essential for achieving high efficiencies. 8 The p-type holetransporting layer (HTL) plays a key role in determining device performance by generating a built-in electric eld at the rear interface and extracting photogenerated holes from the Sb 2 (S,Se) 3 absorber to the counter electrode. Spiro-OMeTAD is the most widely used hole-transporting material (HTM) to date, inheriting from perovskite and dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several groups suggested that an n-i-p device architecture is likely a promising option for Sb 2 X 3 solar cells. [26][27][28][29] Although a lot of works on the fabrication of Sb 2 X 3 absorber with different structures have been done, there is still no consensus on the optimal configuration.…”
Section: Substrate Configurationmentioning
confidence: 99%
“…Therefore, efforts should be made on fabricating highly crystalline antimony chalcogenide absorber films with [hk1] preferred orientation, and less dislocations, which is beneficial to maximize carrier mobility. [ 26 ]…”
Section: Defect Passivationmentioning
confidence: 99%